Mary Edwards Bryan : her early life and works - Brown, Canter; Rivers, Larry E., 1950- (University Press of Florida, 2015)
Mary Edwards Bryan, a Victorian-era southern woman, was an influential and well-respected writer during her time. Brown and Rivers hope to reintroduce her to the world with this "literary" biography --